Effects of Hydrogen Contents on Oxidation Behavior of Alloy 690TT and Associated Boron Accumulation within Oxides in High-Temperature Water. (10th June 2018) - Jeon, Soon-Hyeok; Song, Geun Dong; Hur, Do Haeng
Abstract : The aim of this work is to characterize the oxide layer structure of Alloy 690TT in high-temperature water with different dissolved hydrogen (DH) contents by using an X-ray photoelectron spectroscopy. Under the low DH contents (0.4494–0.8988 mg/kg), the oxide layers were composed of an outermost layer of Ni(OH)2 and Cr(OH)3 enriched in Ni, an intermediate layer of hydroxides and oxides enriched in Cr, and an inner Cr2 O3 layer. Outermost NiO coexists with small amount of Cr2 O3 layer, while in the inner oxide only Cr2 O3 remains. The oxide layers at medium and high DH contents (3.1458– 8.9880 mg/kg) consisted of an outermost layer of Ni(OH)2 and Cr(OH)3 enriched in Cr, an intermediate layer of metallic Ni, hydroxides and oxides enriched in Cr, and an inner Cr2 O3 layer. In addition, boron compounds containing B 3+ ions were accumulated in the thick and porous NiO layer formed at low DH contents, whereas the accumulation of boron compounds did not occur in the thin and dense polyhedral oxide layer formed at medium and high DH contents.